Determinants of Import Demand Functions of Pakistan: An ARDL Bound Testing Approach (International Journal of Business, Economics and Management, 2016)
This study attempts to examine the factors that determine the import demand function of Pakistan using time series data of 1973-2013. Autoregressive Distributed Lag bounds testing approach cointegration is used to determine long run while ECM in ARDL framework to determine short run adjustments. The results showed substantial proof of the existence of a cointegration association at various degrees among variables included in the models.